Beyond Civilizational Dilague, Nipponshi: Ruang Lingkup Identitas Nasional Bangsa Indonesia - Adha, Muhammad Mona; Susanto, Erwin (Universitas Negeri Malang, 2020)
Japanese culture is highly respected and maintained by its citizens. This study aimed to discuss the existence of Japan between 1944 and 1985 and the national identity of the Japanese people. The study used a non-interactive qualitative approach. This study used a non-interactive qualitative research approach, identified and researched concepts, then analyzed data and information about the history and existence of the Japanese nation including its development globally in the midst of international life. Japan, between 1944 and 1985, had entered a new era after the human tragedy, namely the bombing of Hiroshima and Nagasaki. Since the tragedy, Japan had undergone significant changes, namely better infrastructure. Besides, the Japanese were increasingly realizing that they were actually part of Asia. On this basis, the Japanese were called the Neoppons or the New Japanese. Japan’s unique national identity was reflected in the wa-ism philosophy, which was a concept of harmony between individuals and members of society.